Classical Biphasic Pulmonary Blastoma: A Case Report - A Zidane; A Arsalane; A Elktaibi; I Gharassi (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2016)
Pulmonary blastomas are a rare aggressive neoplasms comprising 0.25-0.5% of all primary lung tumors and portend a poor prognosis. Recent World Health Orgnisation (WHO) reclassifications separated well differentiated fetal adenocarcinoma and pleuropulmonary blastoma from classic biphasic pulmonary blastoma which is now among carcinomas with pleomorphic, sarcomatoid or sarcomatous elements. The clinical and radiologic features are nonspecific. Surgery is the standard treatment and the efficacy of adjuvant chemotherapy and radiotherapy has not yet been established. We present a case of classic biphasic pulmonary blastoma in a 52-year old male and review the literature.